'Hurtling down the track': The significance of Australian population debates in an era of anxiety. (December 2015) - Jacobs, Keith
This article focuses on some of the fantasies underpinning contemporary politics and the way that these 'perform', in effect, to occlude more complex understandings. To develop my argument, I deploy a critical discourse analysis to consider the narratives used by politicians during the 2010 Australian Federal election campaign to galvanise popular support by raising the 'threat' posed by large-scale population growth. I argue that narratives framing 'population growth as unsustainable' have a resonance with sections of the electorate because they connect to a sense of unease about the present and the future. The vexed debates surrounding population size are indicative of anxieties that lie beneath the surface of political discourse.